2022
DOI: 10.3389/fnmol.2022.911122
|View full text |Cite
|
Sign up to set email alerts
|

Selective Involvement of a Subset of Spinal Dorsal Horn Neurons Operated by a Prodynorphin Promoter in Aβ Fiber-Mediated Neuropathic Allodynia-Like Behavioral Responses in Rats

Abstract: Mechanical allodynia (pain produced by innocuous stimuli such as touch) is the main symptom of neuropathic pain. Its underlying mechanism remains to be elucidated, but peripheral nerve injury (PNI)-induced malfunction of neuronal circuits in the central nervous system, including the spinal dorsal horn (SDH), is thought to be involved in touch-pain conversion. Here, we found that intra-SDH injection of adeno-associated viral vectors including a prodynorphin promoter (AAV-PdynP) captured a subset of neurons that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Furthermore, we recently highlighted a distinct neuronal subset captured by an AAV incorporating a prodynorphin promoter (AAV-PdynP + ), primarily exhibiting inhibitory characteristics. This subset selectively contributes to the PNI-induced neuropathic allodynia-like behavior evoked by optogenetic Aβ fiber stimulation but not by mechanical stimulation using von Frey filaments (8). Based on our findings, we hypothesized that AAV-NpyP + neurons interact with AAV-PdynP + neurons to produce Aβ fiber-induced allodynia.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…Furthermore, we recently highlighted a distinct neuronal subset captured by an AAV incorporating a prodynorphin promoter (AAV-PdynP + ), primarily exhibiting inhibitory characteristics. This subset selectively contributes to the PNI-induced neuropathic allodynia-like behavior evoked by optogenetic Aβ fiber stimulation but not by mechanical stimulation using von Frey filaments (8). Based on our findings, we hypothesized that AAV-NpyP + neurons interact with AAV-PdynP + neurons to produce Aβ fiber-induced allodynia.…”
Section: Introductionmentioning
confidence: 73%
“…We constructed an AAV expression plasmid pZac2.1 (Penn Vector Core), carrying tdTomato, diphtheria toxin receptors (DTR), enhanced green fluorescent protein (EGFP), mCherry, wheat germ agglutinin (WGA), ChR2 with a rat Npy or Pdyn promoter. AAV-NpyP-tdTomato-WPRE, AAV-PdynP-DTR-EGFP-WPRE, AAV-NpyP-DTR-EGFP-WPRE, AAV-NpyP-mCherry-IRES-WGA-WPRE, AAV-NpyP-ChR2-mCherry-WPRE, AAV-PdynP-tdTomato-WPRE and AAV-PdynP-mCherry-IRES-WGA-WPRE were microinjected into the unilateral side of SDH (7)(8)(9).…”
Section: Aav Vector Production and Intra-sdh Injectionmentioning
confidence: 99%
“…The development of single cell genomics and epigenomics enables further advances in gene therapy, namely tissue-and cell-type-specific targeting, which has complementary applications both for mechanistic studies of neural circuits, and for gene therapy. Targeting dorsal horn subtypes using promoters has shown some success 79,80 , but a particularly compelling strategy is to drive expression of therapeutic transgenes using cell-type-specific enhancers. Previous work has shown the feasibility of this approach in the brain [81][82][83][84] , with most successful approaches being those based on enhancer identification from chromatin accessibility [81][82][83] .…”
Section: Discussionmentioning
confidence: 99%
“…Then, BioMart was used to identify the orthologous human gene, filtering for one-to-one orthologs to avoid potential false positive matches between species. The macaque genome was annotated with orthologous human genes as previously described, motivated by previous successful approaches to annotate more complete gene structures using orthology to human 22,79 . The resulting datasets frame for macaque and mouse contained 15,157 one-to-one orthologs.…”
Section: Comparison Of Macaque and Mouse Snrna-seq Expression Patternsmentioning
confidence: 99%
“…Our results using the ablated mice revealed functions of Aβ-LTMRs in specifically inhibiting mechanical pain transmission. Since multiple studies also suggested functions of Aβ-LTMRs in transmitting mechanical hyperalgesia (Campbell et al, 1988;Ishibashi et al, 2022;Tashima et al, 2018;Xu et al, 2015), we conducted reverse experiments using optogenetic activation of Aβ-LTMRs. Peripheral optogenetic stimulation of Split Cre -Aβ ReaChR mice (Figure 4A) would activate a small population of Aβ-LTMRs innervating the skin area covered by the blue laser light.…”
Section: Local Optogenetic Activation Of Split Cre -Aβ-ltmrs Evoked N...mentioning
confidence: 99%